COMPARATIVE EVALUATION OF ENALAPRIL AND DILTIAZEM EFFICACY IN MENOPAUSAL WOMEN WITH ARTERIAL HYPERTENSION - V. M. Gorbunov; A. D. Deev; E. V. Platonova; M. M. Bystrova (Столичная издательская компания, 2015)
Aim. To compare enalapril (E) and diltiazem (D) efficacy in menopausal women with arterial hypertension (AH) using three methods of blood pressure (BP) measurement. Material and methods. There was a cross-over randomised study with E and D included 22 menopausal women with AH. E was given at a daily dose of 5-20 mg and D - at a daily dose of 180-360 mg. At baseline and at the end of each treatment period ambulatory blood pressure monitoring (ABPM) was carried out. Self blood pressure measurement (SBPM) was performed during all study period. To assess a steadiness of antihypertensive effect we calculated smoothness index and trough-to-peak ratio based on ABPM data. Results. Ambulatory 24-h systolic BP and diastolic BP were decreased in the E group (-15.2/-9.6 mm Hg) and in the D group (-10.9/-6.0 mm Hg). E demonstrated a greater antihypertensive effect on SBPM results in the evening. Values of smoothness index on E treatment were slightly higher than on D treatment (0.86±0.15/0.64±0.13 vs 0.67±0.17/0.62±0.15). Trough-to-peak ratio was inconclusive in this study. Conclusions. Results of the study have shown some advantages of antihypertensive therapy with E compared with these of D in slow release formulation (both drugs at a single daily dose) in menopausal women. A sustained antihypertensive effect without negative influence on circadian BP profile allows to consider E as one of perspective agents for the AH treatment in this type of patients.